Marine-Derived Biocatalysts: Importance, Accessing, and Application in Aromatic Pollutant Bioremediation - Nikolaivits, Efstratios; Dimarogona, Maria; Fokialakis, Nikolas; Topakas, Evangelos (Frontiers in Microbiology, 2017)
The aim of the present review is to highlight the potential use of marine biocatalysts (whole cells or enzymes) as an alternative bioprocess for the degradation of aromatic pollutants. Firstly, information about the characteristics of the still underexplored marine environment and the available scientific tools used to access novel marine-derived biocatalysts is provided. Marine-derived enzymes, such as dioxygenases and dehalogenases, and the involved catalytic mechanisms for the degradation of aromatic and halogenated compounds, are presented, with the purpose of underpinning their potential use in bioremediation. Emphasis is given on persistent organic pollutants (POPs) that are organic compounds with significant impact on health and environment due to their resistance in degradation. POPs bioaccumulate mainly in the fatty tissue of living organisms, therefore current efforts are mostly focused on the restriction of their use and production, since their removal is still unclear. A brief description of the guidelines and criteria that render a pollutant POP is given, as well as their potential biodegradation by marine microorganisms by surveying recent developments in this rather unexplored field.